2014
DOI: 10.3988/jcn.2014.10.3.197
|View full text |Cite
|
Sign up to set email alerts
|

T2 Relaxometry Using 3.0-Tesla Magnetic Resonance Imaging of the Brain in Early- and Late-Onset Restless Legs Syndrome

Abstract: Background and PurposePrevious T2 relaxometry studies have provided evidence for regional brain iron deficiency in patients with restless legs syndrome (RLS). Measurement of the iron content in several brain regions, and in particular the substantia nigra (SN), in early- and late-onset RLS patients using T2 relaxometry have yielded inconsistent results. In this study the regional iron content was assessed in patients with early- and late-onset RLS using magnetic resonance imaging (MRI), and compared the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 27 publications
2
21
1
1
Order By: Relevance
“…In addition, no significant correlation was found between brain tissue magnetic susceptibility and IRLSS in this study. Since only two previous RLS studies reported correlations between MRI based brain iron measure with Johns Hopkins RLS severity score [6, 7], this lack of correlation between magnetic susceptibility and IRLSS can be considered consistent with most other RLS imaging studies [11, 12, 14]. …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In addition, no significant correlation was found between brain tissue magnetic susceptibility and IRLSS in this study. Since only two previous RLS studies reported correlations between MRI based brain iron measure with Johns Hopkins RLS severity score [6, 7], this lack of correlation between magnetic susceptibility and IRLSS can be considered consistent with most other RLS imaging studies [11, 12, 14]. …”
Section: Discussionsupporting
confidence: 77%
“…In one prior study using R2′ as a brain iron measure [7], lower brain iron content in the SN was found only in early-onset RLS patients but not in late-onset RLS patients. Some later studies, however, reported lower SN iron concentrations in late-onset RLS [11, 12], but not in early-onset RLS, either using R2 [15] or R2′[12]. Moreover, there is one study reporting no change in the MRI based iron index (R2* weighted signal intensity) in RLS [16] and another reporting increased iron index (R2) in early-onset RLS without medical treatment [15].…”
Section: Introductionmentioning
confidence: 99%
“…Others evaluated the T2 relaxation time of the substantia nigra, and found low iron content in the pars compacta, but not in the pars reticulata, in patients with late-onset RLS [78]. Recently, the iron index in the substantia nigra was detected as significantly lower in patients with late-onset RLS than in controls, but not in patients with early-onset RLS, in a study using R2′ measurement by 3T MRI [79]. Another group, without differentiating between early-onset and late-onset cases, reported higher mean T2 values, suggesting lower iron content, of multiple regions (caudate head and medial, dorsal, and ventral thalamus) in RLS patients [80].…”
Section: Imaging Findings In Rls Patientsmentioning
confidence: 99%
“…4 Recently, Moon and colleagues detected a significantly lower SN mean iron index in the late-onset RLS compared with control individuals. 5 In addition, Godau and colleagues 6 showed a decreased iron concentration also in the thalamus and caudate nucleus. Reduction in brain iron content in the SN of patients with RLS was also confirmed by means of fMRI ( Fig.…”
Section: Neuroimaging In Restless Legs Syndromementioning
confidence: 97%